Surface Chemistry Analysis of Carbon Nanotube Fibers by X‐Ray Photoelectron Spectroscopy. Issue 19 (11th June 2018) - Alemán, Belén; Vila, Maria; Vilatela, Juan J.
Abstract : Carbon nanotube (CNT) fibers are materials with an exceptional combination of properties, including higher toughness than carbon fibers, electrical conductivity above metals, large specific surface area (250 m 2  g −1 ), and high electrochemical stability. As such, they are a key component in various multifunctional structures combining augmented mechanical properties with efficient interfacial energy storage/transfer processes. This work presents a thorough XPS study of CNT fibers subjected to different purification and chemical treatments, including spatially‐resolved micro XPS synchrotron measurements. The dominant feature is an inherently high degree of sp 2 conjugation, leading to a strong plasmonic band and a semi‐metallic valence band lineshape. This high degree of CNT perfection in terms of longitudinal "graphitization" helps to explain reported bulk properties including the high electrical and thermal conductivity, and accessible quantum capacitance. There is also presence of organic impurities, mostly heavy carbonaceous molecules formed as by‐products during fiber synthesis and which are adsorbed on the CNTs. Sulfur, a promoter used in the CNT growth reaction, is found both in these surface impurities and associated with the Fe catalyst. The observation of strongly‐adsorbed surface impurities is consistent with the high ductility of CNT fibers, attributed to interfacial lubricity. Abstract : A surface chemistry study by XPS of as‐made and purified carbon nanotube (CNT) fibers is assessed. ultra‐high vacuum‐annealing removes impurities, revealing a high degree of sp 2 conjugation, leading to a plasmonic band and semi‐metallic band lineshape. Purified single CNT bundle present a higher regularity of its constituent CNTs. Sulfur, used as a promoter during the growth reaction is found as surface impurity.